Tanggung Jawab Otoritas Jasa Keuangan (OJK) dan Peran Lembaga Perbankan dalam Pengelolaan Dana Corporate Social Responsibility (CSR) Berbasis Good Governance - Wifa Shabilla; Tazkia Widia Ardani; Siti Nurhaliza; Dea Rizki Desambari; Zhafira Nasywa Adriyanasta; Mutiara Laude Amabel; Tri Setiady; Meita Fadhilah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The banking sector is a strategic pillar that supports national economic stability and relies heavily on public trust. To maintain this legitimacy, banks are required to implement Corporate Social Responsibility (CSR), which is not only a moral obligation but also a legal duty as regulated in several laws such as Law No. 40 of 2007 on Limited Liability Companies and Law No. 21 of 2011 on the Financial Services Authority (OJK). This study aims to analyze the responsibility of OJK in managing Corporate Social Responsibility (CSR) funds based on the principles of Good Governance and to examine the role of banking institutions in maintaining public trust through transparent and accountable Corporate Social Responsibility (CSR) practices. This research employs a normative juridical approach by reviewing relevant legislation, literature, and regulatory documents. The results show that OJK holds normative, institutional, and legal responsibilities in supervising Corporate Social Responsibility (CSR) implementation to ensure compliance with the principles of transparency, accountability, independence, responsibility, and fairness. Meanwhile, banking institutions play a crucial role in ensuring that Corporate Social Responsibility (CSR) becomes an integral part of their sustainability strategy rather than a mere administrative formality. The application of Good Corporate Governance (GCG) has a positive impact on increasing public trust, as transparency and accountability in Corporate Social Responsibility (CSR) management strengthen the social legitimacy of banking institutions. Therefore, synergy between OJK and the banking sector in enhancing Corporate Social Responsibility (CSR) governance is the key to achieving an ethical and sustainable financial system.